Patient perspectives of methadone formulation change in British Columbia, Canada: outcomes of a provincial survey. Issue 1 (December 2016) - Greer, Alissa; Hu, Sherry; Amlani, Ashraf; Moreheart, Sarah; Sampson, Olivia; Buxton, Jane
Abstract Background In British Columbia, Canada, methadone maintenance treatment formulation transitioned from the oral liquid compoundTang ™-flavoured methadone to the ten-times more concentrated cherry-flavoured Methadose™ in February 2014. We quantitatively describe perceptions and reported consequences among a sample of patients on methadone maintenance treatment following this transition. Methods A province-wide survey was used. Bivariable analyses utilized independent samplest -tests, Phi associations, and Chi-square tests. Multivariable logistic regression analyses evaluated factors related to dependent variables – namely, increases in dose, pain, dope sickness, and the need to supplement with additional opioids. Results Four hundred five methadone maintenance treatment patients from fifty harm reduction sites across British Columbia reported transitioning to Methadose™ in February 2014. The majority (n = 258; 73.1 %) heard about the formulation change from their methadone provider or pharmacist. Adjusted models show worse taste was positively associated with reporting an increasing dose (OR = 2.46; CI:1.31–4.61), feeling more dope sick (OR = 3.39; CI:1.88–6.12), and worsening pain (OR = 4.65; CI:2.45–8.80). Feeling more dope sick was positively associated with dose increase (OR = 2.24; CI:1.37–3.66), and supplementing with opioids (OR = 8.81; CI:5.16–15.05). Conclusions Methadone maintenance treatment policy changes in British Columbia affect a structurally vulnerable population who may be less able to cope with transitions and loss of autonomy. There may be a psychosocial component contributing to the perception of Methadose™ tasting worse, and increased dope sickness, pain, and dose. Our study shows the pronounced negative impacts medication changes can have on patients without informed, coordinated efforts. We stress the need to engage all stakeholders allowing for communication about the reasons, risks and consequences of medication policy changes and provision of additional psychosocial support.